2020
DOI: 10.1037/cep0000220
|View full text |Cite
|
Sign up to set email alerts
|

The state of transfer of stimulus control after extinction in human instrumental conditioning: A key factor in therapy strategies based in nonhuman animal research.

Abstract: Previous research has shown that instrumental training can encourage the formation of binary associations between the representations of the elements present at the time of learning, that is, between the discriminative stimulus and the instrumental response (the S-R association), between the stimulus and outcome (the S-O association), and between the response and outcome (the R-O association). Studies with rats have used transfer procedures to explore the effects of discriminative extinction (i.e., extinction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Based on the punishment literature and social psychology research, these uncertain feelings act as punishment discriminative stimulus [71,73]. Discriminative stimulus acts as a signal for the individuals to predict whether reinforcement or punishment is forthcoming [74]. Based on the following prediction, humans behave accordingly to attain the reward and avoid the events that they take as aversive.…”
Section: Social and Uncertainty Barriers-punishment Behavioral Litera...mentioning
confidence: 99%
“…Based on the punishment literature and social psychology research, these uncertain feelings act as punishment discriminative stimulus [71,73]. Discriminative stimulus acts as a signal for the individuals to predict whether reinforcement or punishment is forthcoming [74]. Based on the following prediction, humans behave accordingly to attain the reward and avoid the events that they take as aversive.…”
Section: Social and Uncertainty Barriers-punishment Behavioral Litera...mentioning
confidence: 99%
“…Contrary to the general trend in comparative studies regarding nonhuman and human associative learning contents, results in human instrumental conditioning point towards the idea that extinction affects different associative structures in human and nonhuman animals. Gámez and Rosas (2005) used PIT and found that extinction of an instrumental response eliminated the transfer effect, suggesting that human instrumental extinction may be solved by establishing S-NoO associations, rather than by establishing S-No R associations (see also Gámez et al, 2020).…”
Section: The Study Of the Contents Of Learning After Extinctionmentioning
confidence: 99%
“…The next two contributions use traditional psychological laboratory tests to ask questions about the mechanisms of associative learning as applied to foraging ecology (Craft, James, Reaves, & Olson, 2020) and to make comparisons between humans and clinical models for human treatments (Gámez, León, Moreno-Fernández, & Rosas, 2020). Craft et al (2020) tested the effects of successive negative contrast using rats ( Rattus norvegicus ), and the results suggest that animals alter their foraging strategies in ways that may seem contradictory.…”
Section: Contributionsmentioning
confidence: 99%
“…Thus, comparative cognition research conducted in the laboratory informs what may be observed in cognitive ecology studies conducted in the field. Gámez et al (2020) tested transfer of stimulus control after extinction in humans and compared their results with those previously observed in nonhuman animals. The overarching aim of Gámez et al was not only to compare the results of transfer of stimulus control as a scientific exercise but more importantly to delineate differences in underlying associative structure between humans and nonhuman 158 GUILLETTE AND STURDY animals, the latter of which are often used in the laboratory to test potential behavioural-based therapeutic interventions.…”
Section: Contributionsmentioning
confidence: 99%